Spatial Modelling in Forest Ecology and Management A Case Study - Jansen, Martin 1961-; Judas, Michael 1957-; Saborowski, Joachim 1950- (Springer Berlin Heidelberg, 2002)
In this book, GIS-based geomorphological, statistical, and geostatistical methods are used to improve the ecological site description of forest areas. Possibilities and limitations of the regionalization of climatic, soil, and macrofauna point measurements are presented. The resulting maps of indicators provide a broad and precise basis for forest planning and are essential for an integration of ecological and economic aspects of forest management.The applicability for forest practice is exemplified by the delimitation of forest site classes and of forest growth districts as well as the modelling of potential natural woodland communities. A scenario technique was used to simulate the forest stand development in the Harz mountains and to reveal the economic and ecological results of new management guidelines that are favoured by the forest administration. Spatial modelling and GIS-based information and planning systems provide improved data bases that are valuable instruments to describe the consequences of different management guidelines. Thus, they make a major contribution to a fruitful discussion about sustainable forest management